2018
DOI: 10.1002/jmv.25273
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of influenza B virus in Cameroon and high frequency of reassortant strains

Abstract: Influenza B is broadly divided into B/Victoria and B/Yamagata lineages based on its genetic and antigenic properties. We describe in this study the first report on genome characterization of type B influenza virus in the Cameroon National Influenza Center (NIC) between 2014 and 2017. Respiratory samples were collected as part of the influenza surveillance activity in the NIC. RNA products were tested for the presence of influenza using the CDC Influenza A/B typing panel. Thirty-five samples positive for influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…The phylogenetic analysis and IBV lineages detection showed a co-circulation of B/Vic and B/Yam lineages in Senegal, with a predominance of the B/Vic lineage. Similar observations were noted in other countries, such as Australia and New Zealand [ 43 ], Kenya [ 44 ], Italy [ 45 ] and Cameroon [ 46 ]. Analysis of the HA phylogenetic tree showed the circulation of two Yamagata lineage clades (clade 2 and 3) and two Victoria lineage clades (clade 1A and 1B) in Senegal from 2010 to 2019.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The phylogenetic analysis and IBV lineages detection showed a co-circulation of B/Vic and B/Yam lineages in Senegal, with a predominance of the B/Vic lineage. Similar observations were noted in other countries, such as Australia and New Zealand [ 43 ], Kenya [ 44 ], Italy [ 45 ] and Cameroon [ 46 ]. Analysis of the HA phylogenetic tree showed the circulation of two Yamagata lineage clades (clade 2 and 3) and two Victoria lineage clades (clade 1A and 1B) in Senegal from 2010 to 2019.…”
Section: Discussionsupporting
confidence: 86%
“…We also observed that the clade 1A of B/Vic and the clade 3 of B/Yam were the only circulating strains in Senegal since 2012 and 2015, respectively. As observed in Senegal, circulations of B/Vic (clade 1A and 1B) and B/Yam (clades 2 and 3) viruses were reported in several countries, including Kenya [ 44 ], Thailand [ 38 ], Italy [ 45 ], Uruguay [ 36 ], Malaysia [ 30 ], China [ 28 ] and Cameroon [ 46 ]. Nonetheless, the shift in patterns of dominance of the clades can differ from one country to another.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations exhibit that influenza B viruses are genetically more stable, evolve more slowly and undergo antigenic drift less rapidly as compared with type A viruses [30, 31]. The reassortment of gene segments between and within lineages, as well as different deletions, insertions and substitutions, generate the genetic diversity of these viruses and allow them to escape host immunity [3234].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory confirmation techniques were based on molecular detection by realtime reverse transcription polymerase chain reaction for the majority of countries 17 19 , 32 34 , 39 , 49 , 214 . However, countries with national influenza centers used culture and sequencing in addition to the molecular method 48 , 71 , 75 , 82 , 84 , 96 ( Table II ).…”
Section: Resultsmentioning
confidence: 99%